ACCESSIBILITY AND BUILT ENVIRONMENT EFFECTS ON TRANSIT USE - Moniruzzaman, Md (My University, 2011)
A critical factor in transit mode share analysis is the level of accessibility to transit services. The objective of this study is to investigate the relationships between accessibility and the built environment, and the use of transit. To do so, the proportion of transit users is modeled as a function of socio-economic characteristics, transit level of service, and built environment characteristics. While accessibility to transit has been the object of previous research, accessibility by transit is a factor that has received only limited attention in prior transit modal share research. The case study is the city of Hamilton, and the geographic unit of analysis is the Dissemination Area. A logistic model for proportions with a spatial filter (for spatial autocorrelation) and an over-dispersion parameter is found to provide the best fit and statistical properties. The results of analysis at the meso-scale show that accessibility by transit contributes positively to usage of transit. The possibility that factors at the micro-scale may also influence use of transit, suggests the development of a methodology, based on the use of spatial filtering, to systematically select walkability audit sites. The proposed methodology is demonstrated by means of a case study of neighborhoods in Hamilton. Statistical analysis of walkability audit information shows that the proposed selection strategy can be used to better target limited resources for field-based work, and produce valuable insights into the micro-level factors that may affect transit use.
Keywords: Accessibility; Built Environment; Transit Modal Share; Spatial Filter; Walkability Audit; Site Selection; Urban Studies and Planning; Urban Studies and Planning